Findable Accessible Interoperable Re‐usable (FAIR) diffraction data are coming to protein crystallography. Issue 5 (7th May 2019) - Helliwell, John R.; Minor, Wladek; Weiss, Manfred S.; Garman, Elspeth F.; Read, Randy J.; Newman, Janet; van Raaij, Mark J.; Hajdu, Janos; Baker, Edward N.
Abstract : The policy of IUCr Journals on diffraction data is defined. Abstract : The policy of IUCr Journals on diffraction data is defined.